2017
DOI: 10.1177/0897190017740282
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Creatine Kinase due to Potential Drug Interaction With Ticagrelor and Atorvastatin

Abstract: A probable drug-drug interaction occurred with concomitant ticagrelor and atorvastatin. While this interaction may not always be clinically significant, it is reasonable to consider in patients who present with signs and symptoms of adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Creatine kinase elevation and rhabdomyolysis have also been reported in clinical settings (Kido et al. 2015 ; Beavers 2019 ). Since rivaroxaban is a substrate of CYP3A4, the increased systemic exposure of rivaroxaban in our study could be explained by the inhibition effect of ticagrelor on CYP3A4.…”
Section: Discussionmentioning
confidence: 91%
“…Creatine kinase elevation and rhabdomyolysis have also been reported in clinical settings (Kido et al. 2015 ; Beavers 2019 ). Since rivaroxaban is a substrate of CYP3A4, the increased systemic exposure of rivaroxaban in our study could be explained by the inhibition effect of ticagrelor on CYP3A4.…”
Section: Discussionmentioning
confidence: 91%
“…Skeletal muscle damage is associated with the elevation of serum CK levels, regulation of skeletal muscle dysfunction, and fatigue [ 32 ]. Atorvastatin treatment elevates serum CK levels, leads to muscle fatigue, reduces muscular strength, and induces mitochondrial dysfunction [ 33 , 34 , 35 , 36 ]. We found that atorvastatin induced an elevation in serum CK level and fatigue index and reduced maximal forelimb strength ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%